Green GDP vs. Green Growth Index: Comparative Insights for Sustainable Development Metrics - Tomić, Daniel; Dobran Černjul, Anica Dobran (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Green GDP and the Green growth index have emerged as important indicators for evaluating the alignment of economic progress with environmental sustainability. While Green GDP integrates environmental degradation and resource depletion into traditional GDP calculations, the Green growth index reflects a multidimensional approach, incorporating economic, social, and environmental sustainability criteria. This study provides a comparative analysis of these two metrics, focusing on their temporal dynamics and alignment across European countries. Employing cyclical extraction and cross-correlation analysis, the results uncover significant differences in the dynamics of these two indicators, raising questions about their compatibility and reliability for cross-country analysis of green economic progress. Our findings reveal that both indicators, despite their conceptual and methodological differences on one side and similarity in reflecting consistent global patterns of green economy on the other, in fact have different focus, methodology and application possibilities behind them.